Del ejercicio de la prostitución al ejercicio del trabajo sexual como forma de reivindicar derechos negados (2013)
In Bogotá, in the last years, the regulations about prostitution lean towards dignify sex work and give guarantees that such work should have, resulting in a claim for Human Rights, especially for those called on Economic, Social and Cultural Rights.